Pelatihan Tata Kelola Keuangan di Desa Ngaban Kecamatan Tanggulangin: Pelatihan Tata Kelola Keuangan di Desa Ngaban Kecamatan Tanggulangin - Rina Sri Wulandari Rina Sri Wulandari; Medya Ayunda Fitri (Universitas Nahdlatul Ulama Sidoarjo, 2021)
Financial management requires a wise attitude in choosing which needs must bemet first and which needs can be delayed. In Indonesia, family financial management is theresponsibility of a mother. Therefore, the target of the community service being carried outis PKK mothers, namely PKK mothers in Ngaban Village. The purpose of this communityservice is to provide insight into the importance and ways of good (simple) family financialmanagement so that it can meet family needs in the present and the future. Face-to-facemeetings using the lecture method are followed by demonstrations of making simplefinancial reports. The stages of family financial management include several steps that arecarried out, namely determining family financial goals and objectives, re-collectinginformation about family finances, making and developing budget plans, analyzing budgetplans, carrying out budget planning, controlling and evaluating budgetsKeywords: financial governance, financial reports